Characterization and functional reconstitution of a soluble form of the hydrophobic membrane protein lac permease from Escherichia coli. - Roepe, P D (1989)
Lac permease, a polytopic membrane protein from Escherichia coli, has been purified in soluble form by overexpressing the lacY gene by means of the T7 RNA polymerase system. Soluble permease is dissociated from membranes with urea or other chaotropes and appears after the membrane is saturated with newly synthesized permease. Remarkably, this form of the permease appears to remain soluble in phosphate buffer at neutral pH after removal of urea, although it aggregates in a time- and concentration-dependent manner. Importantly, soluble permease behaves as a monomer during size-exclusion chromatography with or without urea, contains less than 3 mol of organic phosphate per mol of protein, and is largely helical. Soluble permease binds p-nitrophenyl alpha-D-galactopyranoside approximately 40% as well as permease in the native environment of the membrane and can be reconstituted into phospholipid vesicles that catalyze lactose counterflow or active transport in response to a membrane potential (interior negative). The results suggest that lac permease can assume a nondenatured conformation in aqueous solution.